Lockdown Fatigue and University Students: Exploring the Factors That Play Significant Roles in the Level of Lockdown Fatigue Among University Students in the Era of COVID-19 - Mohammed, Ali Haider; Hassan, Bassam Abdul Rasool; Wayyes, Abdulrasool M.; Farhan, Sinan Subhi; Al-Ani, Omar Abdulwahid; Blebil, Ali; Dujaili, Juman; Othman, Gamil (Dove Medical Press, 2022)
Background: Due to the COVID-19 global pandemic, the educational sector has undergone a series of changes which have affected both learners and students alike. As a result, the distortion of the students daily routine, isolation, social distancing and potential exposure to the COVID-19 virus changed almost all of the aspects of student life which has led to exhaustion of students, with both psychological and emotional challenges. Therefore, the main aim of this study is to determine the factors that have a significant impact on the level of lockdown fatigue among university students in the era of COVID-19. Methods: A cross sectional was undertaken for this study. A questionnaire was designed and then shared electronically with the respondents of this study. The respondents were 819 students from tertiary institutions in Iraq. Some of the scales used in ranking the responses of the participants are the Lockdown Fatigue scale, Brief Resilience Scale and Coping Behaviours questionnaire. Data analysis was. Results: Overall, the students had a high level of fatigue due to lockdown-measurement. Emptiness was one of the dominant feelings experienced by the students, along with concern for the safety and well-being of their own families. There was general agreement that students take a long time to return to normal routines after stressful events. The students also indicated that they cope with the lockdown through a variety of activities, ranging from making jokes about the situation to putting their faith in a higher power. Male student were less likely to suffer from lockdown-fatigue, however, studying in public university, being from urban areas, and studying in science field are the most significant factors that increase the level of lockdown. However, lower levels of lockdown fatigue were linked to significantly higher levels of personal resilience and coping abilities. Conclusion: High level of lockdown fatigue among students is noticed, and several factors have been identified. Therefore, it is helpful for students to consistently work on reinforcing positive habits which would help them to build resilience when they are subjected to stressful conditions and scenarios.